2023
DOI: 10.3390/ijms24097712
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of the Pea Defensin Psd1 in the Caco-2/Immune Cells Co-Culture upon Candida albicans Infection

Abstract: Candidiasis is one of the most common fungal diseases that can pose a threat to life in immunodeficient individuals, particularly in its disseminated form. Not only fungal invasion but also fatal infection-related inflammation are common causes of systemic candidiasis. In this study, we investigated in vitro immunomodulatory properties of the antifungal pea defensin Psd1 upon Candida albicans infection. Using the real-time PCR, we showed that Psd1 inhibited the antimicrobial peptide HBD-2 and pro-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Immunomodulatory BPs interact with the immune system and can improve its ability to fight off infection by supporting adaptive immune responses through the targeting and upregulating of agents within the body, such as natural killer cells, lymphocytes, and macrophages. The defensin peptide Psd1 in pea has been shown to activate immune cells and increase the immune response of human immune cells [50]. Soymetide-13, a BP from soybean, has been shown to stimulate phagocytosis, which allows the body's immune cells to identify and intercept potential pathogens in the body [51].…”
Section: Comparison Of Bps Across Speciesmentioning
confidence: 99%
“…Immunomodulatory BPs interact with the immune system and can improve its ability to fight off infection by supporting adaptive immune responses through the targeting and upregulating of agents within the body, such as natural killer cells, lymphocytes, and macrophages. The defensin peptide Psd1 in pea has been shown to activate immune cells and increase the immune response of human immune cells [50]. Soymetide-13, a BP from soybean, has been shown to stimulate phagocytosis, which allows the body's immune cells to identify and intercept potential pathogens in the body [51].…”
Section: Comparison Of Bps Across Speciesmentioning
confidence: 99%
“…Psd1 is able to pass through the Caco-2 cell monolayer Trans-epithelial transport assay, using FITC-labelled Psd1 [79] Insignificant changes in cytokine profiles; increase in the production of IL-6, IL-8/CXCL8, and IP-10; induction of expression of genes coding IL-1β, IL-8/CXCL8, and HBD2 It has been shown that plant defensins have immunomodulatory, mainly pro-inflammatory, effects on epithelial cells, which are the first line of defense against pathogens (Table 3). Psd1 upregulates the expression of gene coding human β-defensin-2 (HBD2), IL-1β, and IL-8/CXCL8, as well as increases the production of IL-6 and IP-10 in intestinallike epithelial cells Caco-2 [79]. γ-Thionin upregulates the expression of gene coding membrane receptor TLR2 and cytokines (TNFα, IL-1β, and IL-10), activates the transcriptional factors of inflammatory response (E2F-1, EGR, CBF, AP-1, and others), and increases NO production in bovine mammary epithelial cells (bMECs) [107,108].…”
Section: Psd1mentioning
confidence: 99%
“…The immunomodulatory effects of plant defensins on epithelial cells also persist under infection. Thus, the immunomodulatory effects of Psd1 on Caco-2 cells and γ-thionin on bMECs infected by C. albicans or S. aureus , respectively, are generally the same as those without infection [ 79 , 107 , 108 ]. It is worth mentioning that γ-thionin significantly inhibits S. aureus internalization into bMECs.…”
Section: Plant Defensinsmentioning
confidence: 99%
See 2 more Smart Citations